Leaf and inflorescence production of the wine palm (attalea butyracea) in the dry magdalena river valley, colombia (2013)
The leaves of the wine palm (Attalea butyracea) are collected and harvested along theMagdalena River Valley in Colombia. Young leaves are used as a ceremonial symbol onPalm Sunday, and expanded leaves are used for thatching and for making handicrafts.In order to document leaf production and to evaluate the effect of leaf extraction ongrowth and development, we marked 80 individuals under extractive conditions and40 individuals under non-extractive conditions and we followed leaf production duringseven months. We also studied inflorescence production for one year to evaluate thepotential of A. butyracea as a source of sap for sugar manufacture. Leaf productionin juveniles and sub-adults was correlated to the number of expanded leaves. Leafproduction in adults was correlated with the number of expanded leaves and withstem size. Palms flower throughout the year, and several inflorescences developsimultaneously. The flowering peak occurs during the drier season. Inflorescenceproduction was correlated to the stem height and to the number of expanded leaves,and it is probably affected by leaf harvest. We recommend leaf extraction only fromindividuals with stem over 3 m and with more than 25 expanded leaves. Inflorescenceproduction of A. butyracea gives the palm a potential for sap extraction.